2015
DOI: 10.3906/biy-1406-25
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Vaccinium myrtillus L. (Bilberry) naturally growingin the Turkish flora

Abstract: This study was designed to micropropagate Vaccinium myrtillus L., a naturally growing bilberry, in the Turkish flora. In order to determine the most effective basal medium, lateral buds were initially selected as explants, which were then individually cultured in Murashige and Skoog medium, Anderson's rhododendron medium, and McCown's woody plant medium (WPM) supplemented with 1.0 mg L -1 zeatin in combination with either 0.1 mg L -1 indole-3-butyric acid (IBA) or 0.1 mg L -1 α-naphthalene acetic acid. WPM, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Since the highest values were obtained from the WPM medium in shoot initiation studies, WPM containing various concentrations of cytokinins, auxins, and GA 3 and PGR-free medium were employed in the shoot multiplication studies for bog bilberry. In several reports, researchers suggested WPM medium for high shoot multiplication success (Liu et al, 2008;Cüce and Sökmen, 2015), while MS was suggested as a very effective medium for several Vaccinium species (Gu et al 2009;Cappelletti et al, 2016). In this report, zeatinsupplemented WPM in combination with IBA was found to be most favorable for shoot induction with 63.33% success and the result was similar to our previous report (Cüce and Sökmen, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Since the highest values were obtained from the WPM medium in shoot initiation studies, WPM containing various concentrations of cytokinins, auxins, and GA 3 and PGR-free medium were employed in the shoot multiplication studies for bog bilberry. In several reports, researchers suggested WPM medium for high shoot multiplication success (Liu et al, 2008;Cüce and Sökmen, 2015), while MS was suggested as a very effective medium for several Vaccinium species (Gu et al 2009;Cappelletti et al, 2016). In this report, zeatinsupplemented WPM in combination with IBA was found to be most favorable for shoot induction with 63.33% success and the result was similar to our previous report (Cüce and Sökmen, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Explants excised from different parts of the plant can show very different multiplication success rates because of the differences between the physiological state of the buds on different regions of the stem, as reported by Debnath and McRae (2001a), as well as the natural growth environmental factors and collection time of the explants. The genus Vaccinium has greater variability than other Ericaceae members, and therefore they could need special optimization protocols for micropropagation (Cüce and Sökmen, 2015). As far as our literature survey could ascertain, no comprehensive report is available concerning the comprehensive micropropagation possibilities of V. uliginosum growing in the Turkish flora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…used with the intention of increasing asepsis in explants, especially in the Ericaceae family. In Vaccinium arctostaphylos L. and Vaccinium myrtillus L., surface sterilization with 70% ethanol for 1 minute followed by disinfection for 15 min with 3% sodium hypochlorite showed positive disinfection results (Cüce et al, 2013;Cüce & Sökmen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because of these biological benefits, there is a growing interest in Vaccinium species, and many researchers study the commercial cultivation of these species. Due to the many advantages, including a mass effective clonal propagation, a fully controlled environment, a shortened growth cycle, an uninterrupted production process, and production of disease-free plants, plant tissue culture techniques have recently been preferred for the propagation of these species [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%